2007
DOI: 10.1007/s11294-007-9081-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Education on Job Satisfaction: Independent Single-Equation vs. Structural Equation Models

Abstract: Independent single-equation models and structural equation models are used to analyze both direct and indirect impacts of education length, and of the match between education and employment, on job satisfaction after controlling for individual-specific and job-specific attributes, including health status and wages. The main results show that: (1) education/job mismatches, both in level and domain, reduce utility from work irrespective of schooling years and other individual/job characteristics; (2) the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Particularly notable are the differences in autonomy, task identity and feedback. The finding that the self-employed respondents are more often on average male and older is not surprising based on previous studies (Fabra Florit and Vila Lladosa, 2007;Parker, 2009). …”
Section: Control Variables the Analysis Includes A Number Of Additiomentioning
confidence: 50%
See 1 more Smart Citation
“…Particularly notable are the differences in autonomy, task identity and feedback. The finding that the self-employed respondents are more often on average male and older is not surprising based on previous studies (Fabra Florit and Vila Lladosa, 2007;Parker, 2009). …”
Section: Control Variables the Analysis Includes A Number Of Additiomentioning
confidence: 50%
“…Additionally, their work is based on an officially recognized body of knowledge and skills based on abstract concepts and theories: professional work necessitates involvement in specialized tasks that cannot be performed mechanically (Freidson, 1999;Western et al, 2006). As such, highly-educated professionals arguably benefit from higher levels of job satisfaction than other employees (Huang, 2011), due to their higher expectations of the intrinsic and extrinsic rewards in their jobs and their greater ability to enter such jobs, that is, the indirect effect of 7 education (Fabra Florit and Vila Lladosa, 2007). In this context, recent research points towards fragmentation and downgrading of some forms of professional work.…”
Section: Job Satisfaction Of Professionals and The Effect Of Employmementioning
confidence: 99%
“…The level of job satisfaction of graduates is an overall view after comprehensively considering various factors and it is a key factor for measuring education quality (Yue, 2013). Education can indirectly influence job satisfaction of graduates through various factors including salary and physical conditions (Eugenia and Luis, 2007). Entrepreneurial activity not only can bring material welfare but enhance job satisfaction and well-being (Wim et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, specific skills are not transferable JS can be used to analyse the effect of the EEL on job utility (Vila, 2005;Vila and García-Mora, 2005). In this regard, Fabra Florit and Vila Lladosa (2007) found that employees' perceptions of the relationship between educational level and employment are a determinant of JS. On the one hand, employees that consider themselves to be more skilled in their workstation are less satisfied because their professional development expectations are not achieved.…”
Section: Training and Jsmentioning
confidence: 99%